2020
DOI: 10.1186/s12991-020-00281-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depression among patients with tuberculosis: a systematic review and meta-analysis

Abstract: Background: Evidence has shown that the prevalence of depression is much higher among patients with tuberculosis (TB) and this, in turn, may adversely impact compliance with anti-TB medications. Therefore, this systematic review and meta-analysis aimed to quantitatively summarize epidemiologic evidence on the prevalence of depression among patients with TB and formulate a recommendation for future clinical practice as well as research. Methods: We followed the preferred reporting items for systematic reviews a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 49 publications
(52 reference statements)
9
37
1
2
Order By: Relevance
“…A rare study on mental health and TB from Romania, "Depression and anxiety symptoms among people with rifampicinresistant tuberculosis receiving inpatient care in the National Pulmonology Reference Institute in Romania", reveals the high prevalence (46%) of depression and anxiety among MDR/RR-TB patients, which is comparable with evidence from other studies [26]. An additional research is needed to determine correlation between the prevalence of depression, anxiety and treatment outcomes.…”
Section: Producing Research Evidence To Improve Treatment Outcomesmentioning
confidence: 63%
“…A rare study on mental health and TB from Romania, "Depression and anxiety symptoms among people with rifampicinresistant tuberculosis receiving inpatient care in the National Pulmonology Reference Institute in Romania", reveals the high prevalence (46%) of depression and anxiety among MDR/RR-TB patients, which is comparable with evidence from other studies [26]. An additional research is needed to determine correlation between the prevalence of depression, anxiety and treatment outcomes.…”
Section: Producing Research Evidence To Improve Treatment Outcomesmentioning
confidence: 63%
“…The prevalence estimate is comparable to other studies. In a meta-analysis of 4,903 patients with TB from seven countries, pooled estimated prevalence of depression was 45% (95% CI 38.04-52.55), with higher prevalence among MDR-TB 52.34% (95% CI 38.09-66.22) patients [18]. Other observational studies report the prevalence of depression and depressive symptoms ranging from 19-65% [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Among them two were conducted in Romania and the reported prevalence of depression among hospitalized TB patients was 38.9% [15] and 65% [17]. Results of a meta-analysis study showed that among TB patients the pooled estimated prevalence of depression is 45% [ (18]. The prevalence of depression is higher among RR/MDR-TB patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…The literature points to varying prevalence rates of depression amongst TB patients. A global metaanalysis that aimed to quantitatively summarize the prevalence of depression among TB patients found a pooled estimate of 49.2% from 25 studies (10). 8 of 25 studies in the meta-analysis were from sub-Saharan Africa, namely Nigeria, Cameroon, and Ethiopia, which like Zambia have high TB burdens.…”
Section: Introductionmentioning
confidence: 99%